2005
DOI: 10.1007/s11109-005-4803-9
|View full text |Cite
|
Sign up to set email alerts
|

The Rise and Fall of Political Engagement among Latinos: The Role of Identity and Perceptions of Discrimination

Abstract: This study analyzes how perceptions of discrimination against oneself and/or one's group and whether one self-identifies in national (American), national origin, or panethnic terms affect levels of political engagement among Latinos in the United States. The findings show that perceptions of discrimination against oneself are particularly damaging in that they promote both behavioral and attitudinal alienation (e.g., non-voting and lack of trust), especially among Latinos who identify primarily as American. Be… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

8
139
2
1

Year Published

2009
2009
2020
2020

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 196 publications
(150 citation statements)
references
References 34 publications
8
139
2
1
Order By: Relevance
“…The evidence suggests, however, that Latinos feel even less efficacious than other ethnic and racial groups, although the amplitude of these findings varies depending on whether scholars use internal versus external measures of political efficacy (Michelson 2000;Pantoja and Segura 2003). Research on foreign-born Latinos also indicates that their feelings of political alienation increase over time in the United States and are correlated with perceptions of discrimination (Michelson 2001(Michelson , 2003, though these effects can be mitigated by pan-ethnic self-identification (Schildkraut 2005). Moreover, several scholars of Latino politics have found that descriptive representation may also lessen feelings of political alienation (Pantoja and Segura 2003), especially when Latinos are represented by elected officials who share their same national origin (Sanchez and Morin 2011).…”
Section: Political Alienation Efficacy and Trustmentioning
confidence: 99%
“…The evidence suggests, however, that Latinos feel even less efficacious than other ethnic and racial groups, although the amplitude of these findings varies depending on whether scholars use internal versus external measures of political efficacy (Michelson 2000;Pantoja and Segura 2003). Research on foreign-born Latinos also indicates that their feelings of political alienation increase over time in the United States and are correlated with perceptions of discrimination (Michelson 2001(Michelson , 2003, though these effects can be mitigated by pan-ethnic self-identification (Schildkraut 2005). Moreover, several scholars of Latino politics have found that descriptive representation may also lessen feelings of political alienation (Pantoja and Segura 2003), especially when Latinos are represented by elected officials who share their same national origin (Sanchez and Morin 2011).…”
Section: Political Alienation Efficacy and Trustmentioning
confidence: 99%
“…Duany 2009;Perez 2009;Rodriguez and Menjivar 2009), it is important to note that since Mexicans have had the longest presence and are by far the largest Latino subgroup in the USA, the ways in which they have been (and continue to be) racialized effect how Latinos as a group are viewed by the general American public (De Genova 2004;Chavez 2008;Massey 2009, 15). In terms of the potential impact of the racially and politically charged 2006 immigration policy debate, it is worth pointing out that a hostile anti-immigrant context -even if directed primarily at Mexicans, as it was in 2006 (Chavez 2008) -has been shown to increase political participation (Schildkraut 2005) and help solidify a collective identity among all Latino subgroups (Massey and Sanchez 2010, 2-18). This may explain why during the 2006 protest wave Latinos of all national origin groups expressed similarly high levels of support for the rallies, the vast majority of whom agreed with the statement that "the marches showed that Latinos -immigrants or not -are united and won't put up with discrimination any longer" (Barreto et al 2009, 756).…”
Section: Racialization In Actionmentioning
confidence: 99%
“…While a part of the differential in participation rates across different racial groups can be explained by uneven distribution in resources (Verba et al 1993;Wolfinger and Rosenstone 1980) or varying exposure to mobilization efforts (Rosenstone and Hansen 1993), Latinos and Asian Americans are distinguished from the rest of the electorate in terms of their political opportunities and incentives (e.g., DeSipio 1996). For instance, scholars have found that another set of variables due to their particular status as immigrant-majority and racialminority groups significantly affects their active participation in politics: for instance, length of residence and nativity (Bass and Casper 2001;Lien 2004;Ramakrishnan 2005), English proficiency (Cho 1999), the extent of acculturation (Lien 1994), experiences of discrimination (Schildkraut 2005), group consciousness (Leighley and Vedlitz 1999;Stokes 2003;Uhlaner et al 1989;Wong et al 2005), and religious or non-religious organizational membership (Diaz 1996;Jones-Correa and Leal 2001).…”
mentioning
confidence: 99%